(untitled) (Veterinary Science Development, 2014)
The objective of this study was to determine the reference range values of various biochemical components in serum and synovial fluid in clinically normal young camels (Camelus dromedarius). One-hundred serum samples and 100 synovial fluid samples were collected from clinically, radiographically and cytologically normal carpal, tarsal and fetlock joints. The concentration of blood urea nitrogen (BUN), creatinine, glucose, sodium, calcium, magnesium, chloride, phosphorus, albumin and the activities of creatine kinase, alanine aminotransfearse, aspartate aminotransferase, lactate dehydrogenase and alkaline phosphatase (ALP) were determined using commercially available kits. The concentration and activities of all measured parameters were significantly lower in the synovial fluid than in the serum except for the ALP and phosphorus, which were similar in both serum and synovial fluids. No significant difference was found in any of the measured biochemical parameters in different joints except in ALP activity, which was higher in the tarsal joint in comparison with the carpal and fetlock joint and the BUN concentration, which was higher in the tarsal joint in comparison with the carpal joint. Baseline values for biochemical components of normal camel synovial fluid and their serum counterparts have been generated. Such data can be used in the clinical investigation of camel’s joint diseases.